Konsep Hukum Perbankan Syariah: pola relasi sebagai institusi intermediasi dan agen investasi - Muhamad Sadi Is, S.HI., MH. (Setara, 2015)
Konsep Hukum Perbankan Syariah: pola relasi sebagai institusi intermediasi dan agen investasi